Fingolimod treatment modulates PPARγ and CD36 gene expression in women with multiple sclerosis - Ferret-Sena, Véronique; Capela, Carlos; Macedo, Ana; Salgado, António Vasco; Derudas, Bruno; Staels, Bart; Sena, Armando (Frontiers in Molecular Neuroscience, 2022)
Fingolimod is an oral immunomodulatory drug used in the treatment of multiple sclerosis (MS) that may change lipid metabolism. Peroxisome proliferator-activated receptors (PPAR) are transcription factors that regulate lipoprotein metabolism and immune functions and have been implicated in the pathophysiology of MS. CD36 is a scavenger receptor whose transcription is PPAR regulated. The objective of this study was to evaluate whether fingolimod treatment modifies PPAR and CD36 gene expression as part of its action mechanisms. Serum lipoprotein profiles and PPAR and CD36 gene expression levels in peripheral leukocytes were analyzed in 17 female MS patients before and at 6 and 12 months after fingolimod treatment initiation. Clinical data during the follow-up period of treatment were obtained. We found that fingolimod treatment increased HDL-Cholesterol and Apolipoprotein E levels and leukocyte PPAR and CD36 gene expression. No correlations were found between lipid levels and variations in PPAR and CD36 gene expression. PPAR and CD36 variations were significantly correlated during therapy and in patients free of relapse and stable disease. Our results suggest that PPAR and CD36-mediated processes may contribute to the mechanisms of action of fingolimod in MS. Further studies are required to explore the relation of the PPAR/CD36 pathway to the clinical efficacy of the drug and its involvement in the pathogenesis of the disease.